Effects of different phenylcapsaicin doses on neuromuscular activity and mechanical performance in trained male subjects: a randomized, triple-blinded, crossover, placebo-controlled trial - Jiménez-Martínez, Pablo; Sánchez-Valdepeñas, Juan; Cornejo-Daza, Pedro J.; Cano-Castillo, Clara; Asín-Izquierdo, Iván; Alix-Fages, Carlos; Pareja-Blanco, Fernando; Colado, Juan C. (Frontiers in Physiology, 2023)
Objective: This study aimed to examine the effects of phenylcapsaicin (PC) supplementation on strength performance and neuromuscular activity in young trained males.Materials and methods: Twenty-five trained subjects (full-squat [SQ] 1-repetition maximum [1RM] = 125.6 ± 21.0 kg), enrolled in this randomized, triple-blinded, crossover, placebo-controlled trial. Subjects performed a first session and a post-24h session for each condition. In the first session, subjects ingested a high dose of PC (HD, 2.5 mg), a low dose (LD, 0.625 mg), or a placebo (PLA). Performance in SQ was assessed under a 3x8x70% 1RM protocol in the first session. Performance in countermovement jump (CMJ), SQ with 60% 1RM, and isometric squat were measured before and after the SQ protocol in both sessions. Vastus lateralis (VL) and vastus medialis (VM) neural activity was recorded through surface electromyography (EMG) and averaged in both sessions.Results: Significant differences for condition were reported for lifting velocity, velocity loss and the 60% load in dynamic SQ (p range = 0.02 to 0.04). Electrical changes were not identified for any outcome, although neural activity changed across time (p range ≤ 0.001 to 0.006). A significant condition x time effect was observed in CMJ compared to PLA (p ≤ 0.001) and LD (p ≤ 0.001). Intraset analyses revealed higher velocities in HD compared to LD (p = 0.01) and PLA (p range = 0.004 to 0.008).2 This is a provisional file, not the final typeset article Conclusion: Therefore, PC may improve strength performance and may attenuate the mechanical fatigue induced by resistance training in the SQ and CMJ exercises.